Anthropogenic concentrations of Cd, Ni and Zn in the intertidal and drainage sediments collected from north western Peninsular Malaysia - Yap, Chee Kong; Pang, Bin Huan (Universiti Putra Malaysia Press, 2011)
Surface sediments were collected from the north western intertidal area (14 sites), drainage (3 sites), and rivers (3 sites) of Peninsular Malaysia in April 2005. The samples were analyzed for their concentrations of Cd, Ni, and Zn. The ranges for the total concentrations (µg/g dry weight) of Cd, Ni, and Zn were found to be 0.79-2.48, 6.46-73.92, and 33.6-484.14, respectively. Factory drainage site at Juru exceeded the established sediment quality values (Effect Range Median-ERM) for Zn and Ni, while the concentrations of Zn were also found to have exceeded the ERM at drainages at Kuala Kurau Town and Sg. Juru sites. The geochemical study, based on the sequential extraction technique on the sediments, revealed that the metal percentages of non-resistant fractions of the drainage at Kuala Kurau Town (drainage), Sg. Juru (river), Kuala Juru (intertidal), and factory drainage site at Juru were higher than the resistant fractions of the metals. These indicated that the sites (intertidal, river, and drainages) received anthropogenic inputs of these metals. Therefore, the point source of anthropogenic input in these sites should be given attention in future in order to mitigate the environmental problem on the living resources in the north western of Peninsular Malaysia. The present monitoring data are useful for future establishment of sediment quality guideline for Malaysian aquatic environment.